Penerapan Komponen Tipe CTL (Contextual Teaching Learning) Untuk Meningkatkan Hasil Belajar Peserta Didik Materi Sistem Gerak di SMA Negeri 1 Tondano - Paramitha Penanta; Nova L I M Ogi; Ferny M Tumbel (SOSCIED, 2023)
The research was conducted at SMA Negeri 1 Tondano class XI IPA 1 with the aim of improving student learning outcomes and seeing the suitability of implementing CTL type components in learning. This type of research is Classroom Action Research (PTK) with the application of CTL type components carried out through two cycles. In the first cycle, the average score obtained by students was 77.25 with a percentage of learning outcomes reaching 77.41% and in the CTL type component assessment, conformity was obtained with a percentage of 85.71%. Based on the percentage of learning outcomes that have not reached completeness, the research continues to cycle II. In cycle II, the average score obtained by students was 82.16 with a percentage of learning outcomes reaching 96.77% and in assessing the suitability of CTL type components, a suitability percentage of 100% was obtained. The results of the second cycle of research showed that student learning outcomes increased with a percentage of learning outcomes >85%, so it was concluded that the application of CTL type components could improve student learning outcomes.